Fibrous composite current collector and preparation method thereof, fibrous electrode and battery
By using sleeved annular targets and magnetron sputtering technology to form a metal layer on the surface of the fibrous substrate, the fibrous composite fluid is prepared, which solves the problem of low energy density of the fibrous battery and achieves a higher mass energy density.
Patent Information
- Application Number
- CN202510151192.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-05-13
AI Technical Summary
The energy density of fibrous batteries is lower, mainly due to the one-dimensional structure of the fibrous current collector, which leads to lower loading of the active material.
Two annular targets arranged in sleeve are used to form a metal layer on the surface of the fibrous substrate by magnetron sputtering to prepare multiple continuous fibrous composite fluids to achieve the improvement of the mass energy density of the fibrous battery.
By this method, compared with the traditional wire current collector, the mass of the fibrous composite current collector is lower, which effectively improves the mass energy density of the fibrous battery.
Smart Images

Figure CN119980162A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of fiber-shaped battery manufacturing, and in particular to a fiber-shaped composite current collector and a preparation method thereof, a fiber-shaped electrode and a battery. Background Art
[0002] Fibrous energy storage devices are highly flexible, integrable, and easy to weave, and are expected to be used in the wearable field. They can safely charge mobile phones, electronic watches, and other devices anytime and anywhere. An important unit component of fibrous energy storage devices is the fibrous lithium-ion battery. At present, metal wires are usually used as fibrous current collectors (for example, aluminum wires and copper wires are used as positive and negative current collectors, respectively). However, compared with planar current collectors, the one-dimensional structure of the fibrous current collector results in a lower loading of active materials, which in turn leads to the energy density of fibrous batteries being much lower than that of planar batteries under the same material system. Therefore, how to improve the mass energy density of fibrous batteries has become a major problem at present. Summary of the invention
[0003] The purpose of the present application is to provide a fibrous composite current collector and a preparation method thereof, a fibrous electrode and a battery. The preparation method can realize the continuous production of the fibrous composite current collector. By applying the prepared fibrous composite current collector to a fibrous battery, the mass energy density of the fibrous battery can be improved.
[0004] The embodiment of the present application is implemented as follows:
[0005] In a first aspect, an embodiment of the present application provides a method for preparing a fibrous composite current collector, comprising the following steps: providing a first annular target material and a second annular target material, wherein the first annular target material is sleeved outside the second annular target material with a gap therebetween, a plurality of fibrous substrates are circumferentially arranged and pulled at the gap, and the first annular target material and the second annular target material are formed into a metal layer on the surface of the fibrous substrate by magnetron sputtering, wherein the first annular target material and the second annular target material are made of the same material.
[0006] In the above technical scheme, two annular targets are used to form a relatively closed space in the circumferential area of the two annular targets, so that the ions formed after the target is excited can be more evenly distributed in the gap, and then multiple fibrous substrates are pulled through the gap between the two annular targets, so that the ions can be better deposited on the surface of the multiple fibrous substrates, thereby forming a metal layer with good coating integrity and relatively uniform thickness on the surface of the multiple continuous fibrous substrates, and then preparing multiple continuous fibrous composite current collectors. On this basis, the prepared fibrous composite current collector is applied to fibrous batteries. Compared with the traditional metal wire as the current collector of the fibrous battery, the mass of the fibrous composite current collector of the same diameter is lower, which can effectively improve the mass energy density of the fibrous battery.
[0007] In some optional embodiments, the distance from the center of the fibrous substrate to the inner circumferential wall of the first annular target is D1, the distance from the center of the fibrous substrate to the outer circumferential wall of the second annular target is D2, and D1 is equal to D2.
[0008] In the above technical solution, the fibrous substrate is arranged in the middle of the gap between the two annular targets, that is, the distance between the two targets and substrates is set to be the same, which helps to improve the thickness uniformity of the coating so as to obtain a metal layer with a relatively uniform thickness.
[0009] In some optional embodiments, D1 is 50-200 mm.
[0010] In the above technical solution, the target-substrate distance is limited to a range of 50 to 200 mm, which has the advantages of good ion deposition effect, high deposition efficiency and not easy to cause damage to the fibrous substrate.
[0011] In some optional embodiments, the ratio of the thickness of the first annular target to the thickness of the second annular target is 1:(0.9-1.1).
[0012] In the above technical solution, limiting the thickness ratio of the first annular target material to the second annular target material within the above range helps to improve the uniformity of the coating, thereby preparing a metal layer with a more uniform thickness.
[0013] In some optional embodiments, the fibrous substrate includes a fibrous polymer substrate and a metal bonding layer located on the outer peripheral wall of the fibrous polymer substrate, the material of the metal bonding layer is different from the material of the metal layer, and the density of the metal bonding layer is higher than the density of the metal layer.
[0014] In the above technical solution, a metal bonding layer is added outside the fibrous polymer substrate, and then a metal layer is formed on the surface of the metal bonding layer, which helps to reduce the interface energy difference between the polymer substrate and the metal layer, thereby improving the bonding strength between the metal layer and the polymer substrate.
[0015] In some optional embodiments, the material of the metal bonding layer is selected from at least one of Ni, Cr, Ti, Zr and Fe, and / or the material of the metal layer is selected from at least one of Al, Cu, Li, Zn, Mg, V, Na and K.
[0016] In the above technical solution, the material of the metal bonding layer is selected from the above-mentioned types. These materials can exist stably during the operation of the battery and can more effectively reduce the interfacial energy difference between the polymer substrate and the metal layer, so that the metal layer and the polymer substrate can be combined together for a long time and firmly; in addition, there are many types of applicable materials for the metal layer, which can provide more feasible implementation plans, so that the prepared fibrous composite current collector can be applied to various types of fibrous batteries.
[0017] In some optional embodiments, the thickness of the metal bonding layer is 3 to 50 nm, or / and the thickness of the metal layer is 5 to 30 μm.
[0018] In the above technical scheme, limiting the thickness of the metal bonding layer within the above range can more effectively reduce the interfacial energy difference between the polymer substrate and the metal layer, thereby more effectively improving the bonding strength between the metal layer and the polymer substrate; in addition, limiting the thickness of the metal layer within the above range allows the fibrous composite current collector to have better conductive properties.
[0019] In a second aspect, an embodiment of the present application provides a fibrous composite current collector, which is prepared using the preparation method provided in the embodiment of the first aspect.
[0020] In a third aspect, an embodiment of the present application provides a fibrous electrode, comprising a fibrous composite current collector as provided in the embodiment of the second aspect and an active material layer located on the surface of the fibrous composite current collector.
[0021] In a fourth aspect, an embodiment of the present application provides a fiber-shaped battery, comprising a fiber-shaped electrode provided in the embodiment of the third aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 A schematic diagram of conveying the first fibrous substrate provided in an embodiment of the present application;
[0024] Figure 2 A schematic diagram of conveying the second fibrous substrate provided in an embodiment of the present application.
[0025] Icon: 10-fibrous substrate; 20-first annular target; 30-second annular target; 40-limiting wire dividing disk; 50-gap. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0027] It should be noted that “and / or” in this application, such as “Feature 1 and / or Feature 2”, refers to the three situations of “Feature 1” alone, “Feature 2” alone, or “Feature 1” plus “Feature 2”.
[0028] In addition, in the description of the present application, unless otherwise specified, the meaning of "multiple" in "one or more" refers to two or more; the range of "value a ~ value b" includes the two end values "a" and "b", and the "unit" in "value a ~ value b + unit of measurement" represents the "unit of measurement" of both "value a" and "value b".
[0029] The following is a detailed description of a fibrous composite current collector and a preparation method thereof, a fibrous electrode and a battery in an embodiment of the present application.
[0030] In a first aspect, an embodiment of the present application provides a method for preparing a fibrous composite current collector, comprising the following steps: providing a first annular target material and a second annular target material, wherein the first annular target material is sleeved outside the second annular target material with a gap therebetween, a plurality of fibrous substrates are circumferentially arranged and pulled at the gap, and the first annular target material and the second annular target material are formed into a metal layer on the surface of the fibrous substrate by magnetron sputtering, wherein the first annular target material and the second annular target material are made of the same material.
[0031] In the present application, two annular targets are used to form a relatively closed space in the circumferential area of the two annular targets, so that the ions formed after the target is excited can be distributed more evenly in the gap, and then multiple fibrous substrates are pulled through the gap between the two annular targets, so that the ions can be better deposited on the surface of the multiple fibrous substrates, thereby forming a metal layer with good coating integrity and relatively uniform thickness on the surface of the multiple continuous fibrous substrates, and then preparing multiple continuous fibrous composite current collectors. On this basis, the prepared fibrous composite current collector is applied to fibrous batteries. Compared with the traditional metal wire as the current collector of the fibrous battery, the mass of the fibrous composite current collector of the same diameter is lower, which can effectively improve the mass energy density of the fibrous battery.
[0032] It should be noted that, according to understanding, the fibrous composite current collector is currently temporarily at the laboratory preparation stage. Specifically, it is usually prepared by electrochemical deposition. Since electrodeposition requires a uniform and stable current, and it is difficult to apply a continuous and stable current to the fiber during the continuous production process, the current laboratory stage can only prepare a centimeter-long fibrous composite current collector, and the continuous production of the fibrous composite current collector cannot be achieved. In this application, by pulling the fibrous substrate through the gap between the first annular target and the second annular target, it is conducive to achieving continuous production.
[0033] In order to better understand the technical solution, a schematic diagram of a fiber-shaped substrate is used for auxiliary explanation. Figure 1 , wherein the first annular target 20 is sleeved outside the second annular target 30, and a plurality of fibrous substrates 10 spaced apart along the circumference of the annular target are pulled through the gap 50 between the first annular target 20 and the second annular target 30, so that the first annular target 20 and the second annular target 30 can form a metal layer on the surface of the fibrous substrate 10 by magnetron sputtering; it should be noted that, Figure 1The area marked with number 10 is relatively dense because there are a large number of fibrous substrates 10 in this area. On this basis, in order to prevent multiple fibrous substrates 10 from interfering with each other during transportation and to improve the smoothness of transportation, limited wire separation disks 40 are also provided at both axial ends of the annular target material, so that multiple fibrous substrates 10 enter from the fiber separation disk 40 at one end and pass through the gap 50 between the two annular targets and then pass through the fiber separation disk 40 at the other end, thereby effectively preventing adjacent fibrous substrates 10 from contacting or even overlapping. In addition, a wear-resistant coating is also provided inside the holes in the limited wire separation disk 40, wherein the material of the wear-resistant coating is selected from at least one of epoxy resin, polyurethane and polytetrafluoroethylene, and the provision of a wear-resistant coating helps to better protect the fibrous substrate 10. In the present application, the method of pulling the fibrous substrate 10 is not limited and can be achieved by an ordinary pulling roller.
[0034] As an example, the distance from the center of the fibrous substrate to the inner circumferential wall of the first annular target is D1, and the distance from the center of the fibrous substrate to the outer circumferential wall of the second annular target is D2, and D1 is equal to D2.
[0035] In this embodiment, the fibrous substrate is disposed in the middle of the gap between the two annular targets, that is, the distance between the two targets and the substrates is set to be the same, which helps to improve the thickness uniformity of the coating so as to obtain a metal layer with a relatively uniform thickness.
[0036] As an example, D1 is 50-200 mm, for example but not limited to, D1 is any point value of 50 mm, 60 mm, 70 mm, 80 mm, 90 mm, 100 mm, 120 mm, 140 mm, 160 mm, 180 mm and 200 mm, or a range value between any two of them.
[0037] In this embodiment, the target-substrate distance is limited to a range of 50 to 200 mm, which has the advantages of good ion deposition effect, high deposition efficiency and not easily causing damage to the fibrous substrate.
[0038] As an example, the thickness ratio of the first annular target and the second annular target is 1:(0.9-1.1), for example but not limited to the thickness ratio of any one of 1:0.9, 1:0.95, 1:1, 1:1.05 and 1:1 or a range between any two of them.
[0039] In this embodiment, limiting the ratio of the thickness of the first annular target material to the thickness of the second annular target material to the above range helps to improve the uniformity of the coating, thereby preparing a metal layer with a more uniform thickness.
[0040] As an example, the fibrous substrate includes a fibrous polymer substrate and a metal bonding layer located on the outer peripheral wall of the fibrous polymer substrate. The material of the metal bonding layer is different from that of the metal layer, and the density of the metal bonding layer is higher than that of the metal layer.
[0041] In this embodiment, a metal bonding layer is added outside the fibrous polymer substrate, and then a metal layer is formed on the surface of the metal bonding layer, which helps to reduce the interface energy difference between the polymer substrate and the metal layer, thereby improving the bonding strength between the metal layer and the polymer substrate.
[0042] It should be noted that the source of the fibrous polymer substrate is not limited, and it can be prepared by conventional spinning technology in the art, for example, it can be prepared by solution spinning, melt spinning, wet spinning or dry spinning.
[0043] It should be noted that the material of the fibrous polymer substrate is not limited, and may be, for example, at least one of polyvinylidene fluoride, polyaniline, polypropylene, polyimide, polyethylene terephthalate, and corresponding modified polymers.
[0044] It should be noted that the size of the fibrous polymer substrate is not limited. For example, a fibrous polymer substrate with a diameter of 0.01 to 6 mm (for example, but not limited to, a diameter of any point value among 0.01 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm and 6 mm, or a range between any two of them) can be used.
[0045] It should be noted that there is no limitation on the method of forming a metal bonding layer on a fibrous polymer substrate, for example, vacuum evaporation coating, vacuum sputtering coating and vacuum ion plating can be used. This application takes vacuum sputtering coating as an example for explanation.
[0046] It should be noted that when the preparation method of the metal bonding layer is the same as the preparation method of the metal layer, that is, both adopt the method of magnetron sputtering, the preparation of the two functional layers can be completed independently in two devices, for example, according to Figure 1 The transport schematic shown in the figure is to first prepare a metal bonding layer on a fibrous polymer substrate by magnetron sputtering technology, and then Figure 1 The transport schematic diagram shown in FIG. 1 forms a metal layer on the surface of the metal bonding layer, that is, a fibrous composite current collector is prepared by two independent annular target material assemblies in sequence; it can also be completed in one device, for example, according to Figure 2 The transport schematic diagram shown directly forms a metal bonding layer and a metal layer on the surface of the fibrous polymer substrate in sequence. Figure 2 and Figure 1 The difference is that Figure 2A magnetron sputtering device is equipped with two groups of annular targets. The first group of annular targets is used to form a metal bonding layer on the surface of the fibrous polymer substrate, and the second group of annular targets is used to form a metal layer on the surface of the metal bonding layer. The specific preparation form can be adaptively adjusted according to actual needs.
[0047] As an example, the material of the metal bonding layer is selected from at least one of Ni, Cr, Ti, Zr and Fe, and / or the material of the metal layer is selected from at least one of Al, Cu, Li, Zn, Mg, V, Na and K.
[0048] In this embodiment, the material of the metal bonding layer is selected from the above-mentioned types, which can exist stably during the operation of the battery and can more effectively reduce the interfacial energy difference between the polymer substrate and the metal layer, so that the metal layer and the polymer substrate can be combined together for a long time and firmly; in addition, there are many types of applicable materials for the metal layer, which can provide more feasible implementation plans, so that the prepared fibrous composite current collector can be applied to various types of fibrous batteries.
[0049] As an example, the thickness of the metal bonding layer is 3 to 50 nm, for example but not limited to the thickness of any point value among 3 nm, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm and 50 nm, or the range value between any two thereof; or / and, the thickness of the metal layer is 5 to 30 μm, for example but not limited to the thickness of any point value among 5 μm, 10 μm, 15 μm, 20 μm, 25 μm and 30 μm, or the range value between any two thereof.
[0050] In this embodiment, limiting the thickness of the metal bonding layer within the above range can more effectively reduce the interfacial energy difference between the polymer substrate and the metal layer, thereby more effectively improving the bonding strength between the metal layer and the polymer substrate; in addition, limiting the thickness of the metal layer within the above range allows the fibrous composite current collector to have better conductive properties.
[0051] It should be noted that any process or step not specifically described in the preparation process of the fibrous composite current collector may be arranged according to conventional selection in the art.
[0052] In a second aspect, an embodiment of the present application provides a fibrous composite current collector, which is prepared using the preparation method provided in the embodiment of the first aspect.
[0053] In a third aspect, an embodiment of the present application provides a fibrous electrode, comprising a fibrous composite current collector as provided in the embodiment of the second aspect and an active material layer located on the surface of the fibrous composite current collector.
[0054] In a fourth aspect, an embodiment of the present application provides a fiber-shaped battery, comprising a fiber-shaped electrode provided in the embodiment of the third aspect.
[0055] The features and performance of the present application are further described in detail below in conjunction with the embodiments.
[0056] Example 1
[0057] The present invention provides a method for preparing a fibrous composite current collector, comprising the following steps:
[0058] S1 uses polyethylene terephthalate as the material of the fibrous polymer substrate and adopts solution spinning technology to prepare a fibrous polymer substrate with a diameter of 50 μm.
[0059] S2 then refers to Figure 1 The transport schematic diagram shown first forms a metal bonding layer on the surface of the fibrous polymer substrate, wherein the target material is NiCr, the sputtering power is 0.4kW, the vacuum degree in the vacuum chamber is 0.1Pa, D1 and D2 are equal and 100mm, and the pulling speed is 8m / min to form a NiCr metal bonding layer with a thickness of 30nm.
[0060] S3 continues to refer Figure 1 The transport schematic diagram shown first forms a metal layer on the surface of the metal bonding layer, wherein the target material is Cu, the sputtering power is 5 kW, the vacuum degree in the vacuum chamber is 0.1 Pa, D1 and D2 are equal and are 100 mm, and the pulling speed is 8 m / min to form a Cu metal layer with a thickness of 5 μm and obtain a fibrous composite current collector with a diameter of 60 μm.
[0061] Example 2
[0062] The present invention provides a method for preparing a fibrous composite current collector, comprising the following steps:
[0063] S1 uses polyethylene terephthalate as the material of the fibrous polymer substrate and adopts solution spinning technology to prepare a fibrous polymer substrate with a diameter of 50 μm.
[0064] S2 then refers to Figure 2The transport schematic diagram shown first forms a metal bonding layer on the surface of the fibrous polymer substrate, and then forms a metal layer on the surface of the metal bonding layer, wherein, in the step of preparing the metal bonding layer, the target material is NiCr, the sputtering power is 0.4kW, the vacuum degree in the vacuum chamber is 0.1Pa, D1 and D2 are equal and 100mm, and the pulling speed is 8m / min, so as to form a NiCr metal bonding layer with a thickness of 30nm; in the step of preparing the metal layer, the target material is Cu, the sputtering power is 10kW, the vacuum degree in the vacuum chamber is 0.1Pa, D1 and D2 are equal and 100mm, and the pulling speed is 8m / min, so as to form a Cu metal layer with a thickness of 10μm, and a fibrous composite current collector with a diameter of 70μm is obtained.
[0065] Example 3
[0066] The embodiment of the present application provides a method for preparing a fibrous composite current collector, which differs from Embodiment 2 only in that the pulling speed is 4 m / min to form a Cu metal layer with a thickness of 20 μm to obtain a fibrous composite current collector with a diameter of 90 μm.
[0067] Test example
[0068] The fibrous composite current collectors prepared in Examples 1 to 3 were numbered respectively, and copper wires with the same diameter as in Example 3 were used as controls. The samples were then assembled into fibrous lithium-ion batteries and the mass energy density of each battery was tested. The test results are then statistically reported in Table 1.
[0069] Among them, the steps of battery assembly are as follows:
[0070] S1 uses a high-speed disperser to disperse the lithium cobalt oxide active material, PVDF binder and CNTs conductive agent in N-methylpyrrolidone at a mass ratio of 97:1.5:1.5 and mix them at high speed to obtain a positive electrode slurry; uses a high-speed disperser to disperse the graphite active material, (LA133 and SBR) binder and CNTs conductive agent in water at a mass ratio of 97:(1:0.5):1.5 and mix them at high speed to obtain a negative electrode slurry; at the same time, the electrolyte salt (Li2SO4) is dissolved in a water-soluble polymer polymer (polyvinyl alcohol) to prepare an aqueous gel electrolyte.
[0071] S2 uses each sample as a current collector to pass through the negative electrode slurry, and then enters the micropores to adjust the loading of the negative electrode slurry on the current collector, and obtains the negative electrode fiber after drying; similarly, aluminum wire is used as the positive electrode current collector, quickly passes through the positive electrode slurry, and then enters the micropores to adjust the loading of the positive electrode slurry on the current collector, and obtains the positive electrode fiber after drying.
[0072] The S4 negative electrode fiber is wrapped with an isolation film (PP), and then the wrapped negative electrode fiber and positive electrode fiber are wound into bundles and immersed in a gel electrolyte to ensure that the electrolyte is fully immersed in the positive and negative electrode materials; then it is taken out for drying and packaging to obtain a fibrous battery.
[0073] Table 1
[0074] sample Diameter(μm) Cell weight (g / m) Mass energy density (Wh / kg) Example 1 60 4.21 159 Example 2 70 4.26 157 Example 3 90 4.39 152 Control group (copper wire) 90 4.48 149
[0075] Referring to Table 1, it can be seen from the test results of Example 3 and the control group that when the diameter of the current collector is the same, the fibrous composite current collector prepared by the embodiment of the present application has a better mass energy density than the fibrous battery cell prepared by conventional copper wire.
[0076] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.
Claims
1. A method for preparing a fibrous composite current collector, characterized in that: The following steps are involved: A first annular target material and a second annular target material are provided, wherein the first annular target material is sleeved outside the second annular target material with a gap therebetween, a plurality of fibrous substrates are circumferentially spaced and pulled at the gap, and the first annular target material and the second annular target material are magnetron sputtered to form a metal layer on the surface of the fibrous substrate, wherein the first annular target material and the second annular target material are made of the same material.
2. The method for preparing a fibrous composite current collector according to claim 1, characterized in that: The distance from the center of the fibrous substrate to the inner circumferential wall of the first annular target is D1, and the distance from the center of the fibrous substrate to the outer circumferential wall of the second annular target is D2, and D1 is equal to D2.
3. The method for preparing a fibrous composite current collector according to claim 2, characterized in that: The D1 is 50 to 200 mm.
4. The method for preparing a fibrous composite current collector according to any one of claims 1 to 3, characterized in that: The ratio of the thickness of the first annular target to the thickness of the second annular target is 1:(0.9-1.1).
5. The method for preparing a fibrous composite current collector according to any one of claims 1 to 3, characterized in that: The fibrous base comprises a fibrous polymer substrate and a metal bonding layer located on the outer peripheral wall of the fibrous polymer substrate. The material of the metal bonding layer is different from that of the metal layer, and the density of the metal bonding layer is higher than that of the metal layer.
6. The method for preparing a fibrous composite current collector according to claim 5, characterized in that: The material of the metal bonding layer is selected from at least one of Ni, Cr, Ti, Zr and Fe, and / or the material of the metal layer is selected from at least one of Al, Cu, Li, Zn, Mg, V, Na and K.
7. The method for preparing a fibrous composite current collector according to claim 5, characterized in that: The thickness of the metal bonding layer is 3-50 nm, or / and the thickness of the metal layer is 5-30 μm.
8. A fibrous composite current collector, characterized in that: The method is prepared according to any one of claims 1 to 6.
9. A fiber-shaped electrode, characterized in that: The invention comprises the fibrous composite current collector as claimed in claim 8 and an active material layer located on the surface of the fibrous composite current collector.
10. A fiber-shaped battery, characterized in that: Comprising the fibrous electrode as claimed in claim 9.